INVESTIGATION OF ANTIOXIDANT, α-AMYLASE, α-GLUCOSIDASE INHIBITORY AND ANTIHYPERGLYCEMIC POTENTIALS FROM Physalis angulata L. EXTRACT - Ngo Van Duc; Truong Ngoc Thien Kim; Bui Nguyen Ngoc Ngan; Dinh Thuy Ngoc Anh; Nguyen Ngoc Ngoan; Tran Hoang Ngau (HUIT Journal of Science, 2025)
Diabetes mellitus is a global health issue, and the prevalence of this disease has constantly increased worldwide. The commercial medications used for diabetes in current therapy are limited by their side effects and cost. There is an urgent need to discover antidiabetic agents with minimal or no side effects derived from traditional medicinal plants. Physalis angulata L. is a tropical herbal plant that treats various diseases, including hepatitis, asthma, rheumatism, and malaria. This study investigated the components present in the extract using gas chromatography-mass spectrometry. It evaluated the in vitro antioxidant potential, the α-amylase and α-glucosidase inhibitory properties, along with the in vivo hypoglycemic activity of Physalis angulata L. The results revealed the presence of twenty-six phytochemicals in the extract, with 5-Hydroxymethylfurfural being the most abundant constituent at a percentage area of 29.74%. In the DPPH scavenging assay, the IC50 value of the extract was measured as 962.8 µg/mL. The α-amylase and α-glucosidase inhibitory activities were evaluated, yielding IC50 values of 390.82 µg/mL and 90.82 µg/mL, respectively. The extract significantly decreased blood glucose levels by 48.29% and 47.25% at 200 mg/kg and 400 mg/kg, respectively. In addition, the ethanol extract demonstrated blood glucose reduction following the oral glucose tolerance test in a diabetic mouse model. These findings suggest that the ethanol extract from Physalis angulata L. possesses antioxidant, α-amylase, and α-glucosidase inhibitory activities and anti-hyperglycemic characteristics, making it a consideration for managing diabetes complications and therapeutic purposes.